The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4161/cc.6.16.4574
|View full text |Cite
|
Sign up to set email alerts
|

Gα13 Regulation of Proto-Dbl Signaling

Abstract: Rho family GTPases play important roles in the regulation of intracellular signals induced by activated heterotrimeric G proteins of the α 12/13 family. The α 12/13 subunits activate Rho GTPases through direct binding to a group of Rho guanine nucleotide exchange factors (GEFs) characterized by the presence of a G protein signaling-like (RGL) domain. The Rho GEF proto-Dbl, that does not contain a RGL domain, was also found to link Gα 12/13 signals to Rho. We have explored the effects of activated Gα 13 and Gα … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…7). In this regard, multiple Rho GEFs that have been proposed to link G 12/13 -coupled GPCRs to Rho activation, including PDZ-RhoGEF (PRG), leukemia-associated Rho GEF (LARG), p115-RhoGEF (p115), and lymphoid blast crisis (Lbc), its longer transcript fused to an AKAP (A kinase anchor protein), AKAP-Lbc (8,9), proto-Dbl (10,11), and Lfc (12). Among them, PRG, LARG, and p115 share the presence of a RGS homology domain, which is responsible for their interaction with G␣ 12 and its family member, G␣ 13 (6,8,13).…”
mentioning
confidence: 99%
“…7). In this regard, multiple Rho GEFs that have been proposed to link G 12/13 -coupled GPCRs to Rho activation, including PDZ-RhoGEF (PRG), leukemia-associated Rho GEF (LARG), p115-RhoGEF (p115), and lymphoid blast crisis (Lbc), its longer transcript fused to an AKAP (A kinase anchor protein), AKAP-Lbc (8,9), proto-Dbl (10,11), and Lfc (12). Among them, PRG, LARG, and p115 share the presence of a RGS homology domain, which is responsible for their interaction with G␣ 12 and its family member, G␣ 13 (6,8,13).…”
mentioning
confidence: 99%
“…Activation of Rho, in response to LPA, is thought to involve stimulation of the ␣-subunit of the heterotrimeric G 12 /G 13 proteins that act on a family of highly related Rho-specific GEFs, including p115-RhoGEF, PDZ-Rho-GEF, and LARG (32)(33)(34). Moreover, we have shown that activated G␣ 13 induces activation of the GEF Dbl stimulating its association with ezrin (14). The two mechanisms by which Rho acts both upstream and downstream of ERM proteins are compatible with a system that creates a positive feedback loop which promotes activation of Rho by ERM association with hamartin and/or by inhibition of Rho GDI.…”
mentioning
confidence: 61%
“…NIH-3T3 cells were stably cotransfected with onco-Dbl together with shham or sh-ns. Cell lysates were obtained and processed as previously described (14). Immunoprecipitation was performed by incubating cell lysates with polyclonal anti-GST antibody (Molecular Probes) to detect GST-Dbl fusion proteins, monoclonal anti-ezrin antibody (Santa Cruz Biotechnology), polyclonal anti-hamartin antibody (Santa Cruz Biotechnology) for detection of endogenous and FL-ham, or with monoclonal antibody against Xpress epitope (Invitrogen), for detection of ⌬-ham.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations